Interplanetary magnetic field and solar cycle dependence of Northern Hemisphere F region joule heating. Issue 2 (27th February 2015) - Bjoland, L. M.; Chen, X.; Jin, Y.; Reimer, A. S.; Skjæveland, Å.; Wessel, M. R.; Burchill, J. K.; Clausen, L. B. N.; Haaland, S. E.; McWilliams, K. A.
Abstract Joule heating in the ionosphere takes place through collisions between ions and neutrals. Statistical maps of F region Joule heating in the Northern Hemisphere polar ionosphere are derived from satellite measurements of thermospheric wind and radar measurements of ionospheric ion convection. Persistent mesoscale heating is observed near postnoon and postmidnight magnetic local time and centered around 70° magnetic latitude in regions of strong relative ion and neutral drift. The magnitude of the Joule heating is found to be largest during solar maximum and for a southeast oriented interplanetary magnetic field. These conditions are consistent with stronger ion convection producing a larger relative flow between ions and neutrals. The global‐scale Joule heating maps quantify persistent (in location) regions of heating that may be used to provide a broader context compared to small‐scale studies of the coupling between the thermosphere and ionosphere.